Tinjauan Kritis Neurosains Terhadap Konsep Qalb Menurut Al-Ghazali - Muhammad Nasruddin; Abdul Muiz (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2020)
The human body was created very special by God. inside there is a special body part in the form of the brain, and neuroscience is the science that discusses in full the brain from various scientific disciplines. In the study of Islam, qalb is the most important part in the good and bad quality of human faith which is studied in depth in Sufism to the purity of the soul. And Imam Al-Ghazali became one of the Sufi figures who explained in detail about the Qalb. That neuroscience views qalb in Islam as part of the human brain, on the functional basis between the brain and qalb both receive information, spiritual intelligence / qalbiah, spiritual, controlling / coordinating center of the body, and emotional. The brain and qalb, according to Al-Ghazali, both have similarities in the four elements namely controlling the body, knowledge, emotions, and spirituality. And the difference between the two, namely the two different dimensions between the scientific and divine dimensions, so the benchmarks of truth are very different.